Classification and feature extraction of binucleate cells using Mahalanobis distance and Gabor wavelet analysis. (1st January 2014) - Afrin, Kahkashan
A hybrid methodology of feature extraction and classification is proposed in this paper to classify binucleate and non-binucleate or normal cells. The proposed methodology consists of a Gabor filter-based feature extraction using two types of Gabor filters, namely circular Gabor and Gabor wavelet. Feature matrix considering mean and variance are calculated in sets of 50 for each of the filters. Thereafter, dimensionality reduction is done using a binary particle swarm optimisation (BPSO) technique to screen out the redundant features. Finally, Mahalanobis distance (MD) is used to classify the images into respective classes using the reduced set of features. To show the efficacy and robustness of the proposed hybrid technique using Gabor wavelets, the classification accuracy is calculated and compared with circular Gabor.